PENGARUH REKRUTMEN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT STAR ABADI RATU INDONESIA BOGOR JAWA BARAT - Fizna Rafsanjani; Melda Wiguna (Journal of Research and Publication Innovation, 2025)
This study aims to determine partially and simultaneously the effect of Recruitment and Training on Employee Performance at PT Star Abadi Ratu Indonesia Bogor West Java. This type of research uses Quantitative Method with associative approach. Data collection techniques in this study use observation techniques, questionnaires and library studies. Data obtained by the questionnaire were analyzed using SPSS version 26 calculations, at a significance level of a 5% hypothesis test. This research was conducted at PT Star Abadi Ratu Indonesia Bogor West Java. Based on the results of this study, there is a significant influence partially and simultaneously between Recruitment and Training on Employee Performance. The Recruitment hypothesis test obtained a value of tcount>ttable (7.350> 1.674) tcount is greater than ttable with a significance value of 0.000 which means less than 0.05 (0.000 <0.05). Training Hypothesis Test obtained tcount>ttable (10.156>1.674) tcount is greater than ttable with a significance value of 0.000 which means it is smaller than 0.05 (0.000<0.05). And the Recruitment and Training hypothesis test obtained Fcount>Ftable (60.138>3.17) Fcount is greater than Ftable with a significance value of 0.000 which means it is smaller than 0.05 (0.000<0.05) thus Hₒ is rejected and Hₐ is accepted meaning that both partially and simultaneously recruitment and training have a significant effect on employee performance at PT Star Abadi Ratu Indonesia Bogor West Java